Assessment of Risk Factors for the Occurrence of a High-Output Ileostomy - Seifarth, Claudia; Augustin, Leonard N.; Lehmann, Kai S.; Stroux, Andrea; Lauscher, Johannes C.; Kreis, Martin E.; Holmer, Christoph (Frontiers in Surgery, 2021)
Background: Ileostomy is often required in patients undergoing bowel resections for inflammatory bowel diseases (IBD), colorectal cancer and emergencies. Unfortunately, some patients develop a high-output stoma (HOS). This condition affects homeostasis and may be life threatening. We aimed to identify possible risk factors for the development of HOS. Patients and methods: From 2012 to 2018, 296 patients who underwent ileostomy at Charité – Universitätsmedizin Berlin, Campus Benjamin Franklin were retrospectively analyzed. Emergency operations were included. Diverting ileostomy, end ileostomies and anastomotic stomata with at least part ileum, were examined. HOS was defined as stoma output of more than 1000 ml per day for more than three days. Univariate and multivariable analyses were used to detect potential risk factors for the development of HOS. Results: 41 of 296 patients developed HOS (13.9 %). Mortality was 0.3 %. In the univariate analysis, age (p < 0.001), diagnosis (Crohn’s disease, p = 0.002), arterial hypertension (p = 0.021), surgical procedure (right-sided colectomy, small bowel resection, p < 0.001), open technique (p < 0.001), emergencies (p = 0.012) and anastomotic ileostomy (p < 0.001) were identified as risk factors. In the multivariable logistic regression, older age, diagnosis (Crohn’s disease) and surgical procedure (right-sided colectomy, separate ileostomy, small bowel resection) remained significant risk factors. Conclusion: The occurrence of HOS is a relevant problem after ileostomy. The identification of risk factors for a high-output may be helpful for monitoring, early diagnosis and initiation of therapy as well as in the planning of close follow-up care.